A practical method for estimating climate-related changes to riverine flood elevation and frequency. Issue 3 (16th February 2023) - Maimone, Mark; Adams, Tim
Abstract: Floods have been occurring with increasing frequency, leading to damage to communities worldwide. These impacts are expected to continue to rise due to increases in the intensity of extreme rainfall. Global climate model (GCM) output, while imperfect in reproducing daily rainfall, is the only practical source of future projections of extreme rainfall intensification. This article presents a practical method for translating GCM precipitation output into usable outputs for stormwater and flood management planning at a regional or local level. The method estimates the impact of extreme storm intensification on riverine flooding using available runoff estimates from GCM precipitation and variable infiltration capacity models, focusing on changes in elevation and frequency due to climate change. It allows communities and utilities to obtain a screening-level estimate of climate change impacts to peak discharge rate statistics without conducting hydrologic modeling. This article outlines the method, its implementation for the 48 contiguous states of the United States, and an example calculation for a river in the eastern United States. Changes in extreme storm runoff intensity vary significantly by region, but much of the United States is projected to see increases of 25 and 50% by 2060 and 2090, respectively, for the RCP8.5 scenario. HIGHLIGHTS: Provides estimates of percent increases in runoff and precipitation by decade from 2020 to 2090 for the United States. Outlines a method to use existing hydraulic models to estimate changes future flood elevations based on the projected increases to runoff. Future increases in runoff will be significantly larger than the more-often-studied percent increases in precipitation. By the end of century, a significant fraction of the southern and eastern portions of the United States can expect runoff increases of 30% or more for RCP4.5 and 50% or more for RCP8.5. Graphical Abstract